Azilsartan inhibits inflammation-triggered bone resorption and osteoclastogenesis in vivo via suppression of TNF-α expression in macrophages - Fan, Ziqiu; Kitaura, Hideki; Ren, Jiayi; Ohori, Fumitoshi; Noguchi, Takahiro; Marahleh, Aseel; Ma, Jinghan; Kanou, Kayoko; Miura, Mariko; Narita, Kohei; Lin, Angyi; Mizoguchi, Itaru (Frontiers in Endocrinology, 2023)
Introduction: Hypertension is a major risk factor for cardiovascular disease (CVD) and is associated with increased bone loss due to excessive activity of the local renin-angiotensin system (RAS). Angiotensinogen/Angiotensin (ANG) II/Angiotensin II type 1 receptor (AT1R) axis is considered as the core axis regulating RAS activity. Azilsartan is an FDA-approved selective AT1R antagonist that is used to treat hypertension. This study aimed to determine whether azilsartan affects formation of osteoclast, resorption of bone, and the expression of cytokines linked with osteoclastogenesis during lipopolysaccharide (LPS)-triggered inflammation in vivo. Methods: In vivo, following a 5-day supracalvarial injection of LPS or TNF-α with or without azilsartan, the proportion of bone resorption and the number of tartrate-resistant acid phosphatase (TRAP)-positive multinucleated cells, which are identified as osteoclasts on mice calvariae were counted. The mRNA expression levels of TRAP, cathepsin K, receptor activator of NF-κB ligand (RANKL), and TNF-α were also evaluated. In vitro, the effect of azilsartan (0, 0.01, 0.1, 1, and 10 M) on RANKL and tumor necrosis factor-alpha (TNF-α)-triggered osteoclastogenesis were investigated. Also, whether azilsartan restrains LPS-triggered TNF-α mRNA and protein expression in macrophages and RANKL expression in osteoblasts were assessed. Furthermore, western blotting for analysis of mitogen-activated protein kinases (MAPKs) signaling was conducted. Results: Azilsartan-treated calvariae exhibited significantly lower bone resorption and osteoclastogenesis than those treated with LPS alone. In vivo, LPS with azilsartan administration resulted in lower levels of receptor activator of RANKL and TNF- mRNA expression than LPS administration alone. Nevertheless, azilsartan did not show inhibitory effect on RANKL- and TNF-α-triggered osteoclastogenesis in vitro. Compared to macrophages treated with LPS, TNF- mRNA and protein levels were lower in macrophages treated by LPS with azilsartan. In contrast, RANKL mRNA and protein expression levels in osteoblasts were the same in cells co-treated with azilsartan and LPS and those exposed to LPS only. Furthermore, azilsartan suppressed LPS-triggered MAPKs signaling pathway in macrophages. After 5-day supracalvarial injection, there is no difference between TNF-injection group and TNF-with azilsartan injection group. Conclusion: These findings imply that azilsartan prevents LPS-triggered TNF- production in macrophages, which in turn prevents LPS-Triggered osteoclast formation and bone resorption in vivo.